Search for third generation scalar leptoquarks in pp collisions at s√=7s=7 TeV with the ATLAS detector - Aad, G. (2013)
A search for pair-produced third generation scalar leptoquarks is presented, using proton-proton collisions at s√=7s=7 TeV at the LHC. The data were recorded with the ATLAS detector and correspond to an integrated luminosity of 4.7 fb−1. Each leptoquark is assumed to decay to a tau lepton and a b-quark with a branching fraction equal to 100%. No statistically significant excess above the Standard Model expectation is observed. Third generation leptoquarks are therefore excluded at 95% confidence level for masses less than 534GeV.